A W-Band 1-dB Insertion Loss Wilkinson Power Divider Using Silicon-Based Integrated Passive Device - Hsiao, Chiao-Yun; Wu, Chung-Tse Michael; Kuo, Chien-Nan (IEEE microwave and wireless components letters, 2021)
This work presents an on-chip Wilkinson power divider using silicon-based integrated passive device (IPD) technology that operates from 70 to 110 GHz, thereby covering the entire W -band (75-110 GHz). Based on a simple impedance transformation different from the conventional Wilkinson power divider topology, the proposed silicon IPD power divider with a core size of 0.417 mm 2 can demonstrate power loss of less than 1.1 dB along with input-output return loss better than 14 dB throughout the entire band.